The edges of the earth in ancient thought : geography, exploration, and fiction - Romm, James S. (Princeton, N.J. : Princeton University Press, 1992)
The "edges of the earth" became the basis of a literary tradition, surveyed here, revealing that the Greeks, and to a somewhat lesser extent the Romans, saw geography not as a branch of physical science but as an important literary genre.
Introduction: Geography as a Literary Tradition -- The Boundaries of Earth -- Boundaries and the Boundless -- Ocean and Cosmic Disorder -- Roads around the World -- Herodotus and the Changing World Picture -- Aristotle and After -- Ethiopian and Hyperborean -- The Blameless Ethiopians -- The Fortunate Hyperboreans -- Arimaspians and Scythians -- The Kunokephaloi -- Wonders of the East -- Before Alexander -- Marvel-Collectors and Critics -- The Late Romance Tradition -- Ultima Thule and Beyond -- Antipodal Ambitions -- The North Sea Coast -- The Headwaters of the Nile -- The Atlantic Horizon -- Geography and Fiction -- Ocean and Poetry -- The Voyage of Odysseus -- Pytheas, Euhemerus, and Others -- The Fictions of Exploration -- Epilogue: After Columbus.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Classical literature -- History and criticism; Geography in literature; Littérature ancienne -- Histoire et critique; Géographie dans la littérature.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; HISTORY -- Ancient -- General; Classical literature; Geography in literature; Antike; Exotismus; Literatur; Weltbild; Weltende; Klassieke oudheid; Wereldbeeld; Geografia (historia); Miscelanea grega (literatura); Miscelanea latina (literatura); Littérature antique -- Thèmes, motifs; Géographie -- Dans la littérature.; Géographie -- Histoire; Géographie antique; Terre -- Dans la littérature.; Géographie dans la littérature.; Ideengeschichte Anfänge-500.; Geschichte 800 v. Chr.-200.; Classical literatures -- Special subjects -- Geography; Nonfiction; Criticism, interpretation, etc